Earthworms are little affected by reduced soil tillage methods in vineyards - Florian FABER; Elisabeth WACHTER; Johann G. ZALLER (Plant, Soil and Environment, 2017)
Inter-rows in vineyards are commonly tilled in order to control weeds and/or to conserve water. While impacts of tillage on earthworms are well studied in arable systems, very little is known from vineyards. In an experimental vineyard, the impact of four reduced tillage methods on earthworms was examined: rotary hoeing, rotary harrowing, grubbing and no tillage. According to an erosion prevention programme, tillage was applied every other inter-row only while alternating rows retained vegetated. Earthworms were extracted from the treated inter-rows 10, 36, 162 and 188 days after tillage. Across dates, tillage methods had no effect on overall earthworm densities or biomass. Considering each sampling date separately, earthworm densities were affected only at day 36 after tillage leading to lower densities under rotary hoeing (150.7 ± 42.5 worms/m2) and no tillage (117.3 ± 24.8 worms/m2) than under rotary harrowing (340.0 ± 87.4 worms/m2) and grubbing (242.7 ± 43.9 worms/m2). Time since tillage significantly increased earthworm densities or biomass, and affected soil moisture and temperature. Across sampling dates, earthworm densities correlated positively with soil moisture and negatively with soil temperature; individual earthworm mass increased with increasing time since tillage. It was concluded that reduced tillage in vineyards has little impact on earthworms when applied in spring under dry soil conditions.